Comparison of the effects of citicoline and vascular rehabilitation capsules on neurotrophic and inflammatory factors in patients with cerebral infarction - Wu Dongyun; Pan Jiajun; Fang Xinhong; Chen Zhongjun (Journal of Medical Biochemistry)
Background: Butylphthalide (BP) is commonly used to treat vascular dementia (VD) following cerebral infarction (CI), but BP alone has limited efficacy. BP in combination with citicoline (COPC) or vascular rehabilitation capsules (VRC) is common in clinical practice, but few studies have compared the differences between these two treatment options. Methods: Ninety-eight patients with VD after CI who were seen in our hospital from April 2020 to June 2022 were selected as the study population. Among them, 52 patients received BP combined with COPC (BP+COPC group), while the rest 46 received BP combined with VRC (BP+VRC group). Fasting venous blood was drawn from the patients before and after treatment. The levels of neurotrophic factor [nerve growth factor (NGF), neuron-specific enolase (NSE), brain-derived neurotrophic factor (BDNF)], oxidative stress [superoxide dismutase (SOD), malondialdehyde (MDA)], and inflammatory factors [Tumor necrosis factor-a (TNF-a), Interleukin-1 (IL-1b), C-reactive protein (CRP)] were measured. Cognitive and neurological improvements were assessed using the Loewenstein Occupational Therapy Cognitive Assessment (LOTCA) and the National Institute of Health Stroke Scale (NIHSS). In addition, the patient's cerebral hemodynamics were examined by CT. Results: After treatment, LOTCA increased in both groups and was higher in the BP+COPC group than in the BP+VRC group (P<0.05), while NIHSS decreased in the BP+COPC group than in the BP+VRC group (P<0.05). NSE, MDA, IL-1 , CRP, and TNF-a decreased in both groups after treatment, while NGF, BDNF, and SOD increased, again with more significant changes in the BP+COPC group (P<0.05). In addition, cerebral hemodynamics was more favourable in the BP+COPC group than in the BP+VRC group (P<0.05). Conclusions: BP combined with COPC has superior improvement in neurologic function in patients with VD after CI.